In situ anticariogenic potential of glass lonomer cement - Benelli, E. M.; Serra, M. C.; Rodrigues, A. L.; Cury, J. A. (Karger Publishers, 1993)
The purpose of this study was to compare the amount of fluoride in plaque formed on glass ionomer cement or composite and to evaluate the effects of fluoride released on growth of cariogenic microflora, fluoride uptake, and secondary caries formation under in situ conditions of a high cariogenic challenge. Ten adult volunteers took part in this crossover study performed in two phases of 28 days. Eighty enamel blocks were randomly restored with glass ionomer cement (Chelon-Fil-Espe) or composite (Silux). During each phase of the study, an acrylic resin appliance, containing four enamel blocks restored with the same material, was constructed for each of the volunteers. During the experimental period, all subjects used fluoride-free dentifrice, refrained from brushing the restored enamel blocks, and immersed the appliances into 20% sucrose solution eight times a day. Fluoride levels, mutans streptococci, and lactobacilli were assessed in dental plaque. Fluoride uptake and microhardness profiles were determined in enamel around the restorations. Statistical analyses indicated a significantly higher level of fluoride (p < 0.05) and a lower level of mutans streptococci plaque formed on glass ionomer cement. Analysis of variance in a split-plot model indicated that in the enamel around the glass ionomer restoration the fluoride uptake was significantly greater (p<0.025) and the mineral loss significantly lower (p<0.01). The results show that glass ionomer cement presents a broad anticariogenic effect and may be of value in preventing secondary caries, even under conditons of a high caries risk. © 1993 S. Karger AG, Basel.
Keywords: Enamel; Fluoride; Glass ionomer cement; Lactobacilli; Mutans streptococci; Plaque